2008
DOI: 10.1128/aac.00470-07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphonated Carbocyclic 2′-Oxa-3′-Aza-Nucleoside on Human T-Cell Leukemia Virus Type 1 Infection In Vitro

Abstract: The human T-cell leukemia/lymphoma virus type 1 (HTLV-1) is an oncogenic retrovirus endemic in certain areas of the world including Japan and North and South America, where about 5% of the estimated 20 million HTLV-1-infected people develop HTLV-1-associated diseases (10,11,43), such as adult T-cell leukemia (ATL), human myelopathy/tropical spastic paraparesis (/TSP), or other minor inflammatory diseases. A number of studies have shown that HTLV-1 infects different types of cells (e.g., lymphocytes, monocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…HTLV-1 infection was carried out as previously shown. 26 Peripheral blood mononuclear cells were co-cultivated with a HTLV-1 chronically infected cell line and infection was evaluated as production of the viral core protein p19. HIV infection was carried on by using a stable T cell line (CEM) containing a plasmid encoding a green fluorescence protein (GFP) driven by the HIV-1 long terminal repeat.…”
Section: Biological Assaymentioning
confidence: 99%
“…HTLV-1 infection was carried out as previously shown. 26 Peripheral blood mononuclear cells were co-cultivated with a HTLV-1 chronically infected cell line and infection was evaluated as production of the viral core protein p19. HIV infection was carried on by using a stable T cell line (CEM) containing a plasmid encoding a green fluorescence protein (GFP) driven by the HIV-1 long terminal repeat.…”
Section: Biological Assaymentioning
confidence: 99%
“…7 First, we tested the reliability of our HTLV-1 RT assay using serial dilution of MT2 supernatants mimicking conditions of those from ATL PBMC cultures. DNA extracted from cells harvested after 10 days in culture was used for HTLV-1 clonality analysis of samples collected before and after therapy for 1 representative responder patient and 1 nonresponder patient (details of the assays and of the preliminary tests are given in supplemental Methods).…”
Section: Cell Cultures and Quantification Of Virological Parametersmentioning
confidence: 99%
“…Allogeneic stem cell transplantation can result in long-term disease control but few patients can be successfully transplanted. 3 Antiretrovirals with activity against HIV-1, such as zidovudine (39-azido-29,39-dideoxythymidine [AZT]) and tenofovir, and new phosphonated compounds, efficiently block HTLV-1 transmission in vitro, [4][5][6][7] whereas HTLV-1 was resistant to lamivudine. 8 Two preliminary phase 2 studies using the combination of AZT and interferon-a (IFN-a) reported an unexpectedly high response rate, particularly in previously untreated acute ATL patients.…”
Section: Introductionmentioning
confidence: 99%
“…12 In this context we have tried to synthesize phosphonated N,O-homonucleosides 13c and 14c, starting from the phosphonated nitrone 12. However, in the cycloaddition reaction of 12 with compound 9 no significant amounts of cycloadducts were detected in the crude reaction mixture (entry 5) under traditional heating.…”
Section: Resultsmentioning
confidence: 99%